Merawat Kearifan Lokal Lamaholot : Studi pada UMKM Qwatex Handycraf - Brigita Elisabet KR. Uran (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
East Flores Regency possesses a rich diversity of local wisdom, including ikat weaving, oral traditions, and various cultural practices that hold significant potential for development within the creative economy sector. The utilization of this local wisdom by Micro, Small, and Medium Enterprises (MSMEs) not only contributes to improving community welfare but also serves as a means of cultural preservation. This study aims to analyze the role of Qwatex Handycraft MSME in preserving Lamaholot local wisdom while simultaneously acting as a driver of the local economy. The research employs a descriptive qualitative approach, with data collected through interviews and document analysis. Data analysis is conducted through the stages of data reduction, data display, and conclusion drawing. The findings reveal that Qwatex Handycraft plays a strategic role in cultural preservation by developing ikat-based products combined with modern design innovations. In addition, this MSME contributes to the local economy by empowering weaving artisans and surrounding communities, thereby creating employment opportunities and increasing income levels. Another significant role is its educational function, introducing cultural values to younger generations through creative products that align with contemporary trends. However, the business still faces several challenges, including limited capital, low digital literacy, and restricted market access. Therefore, continuous support from the government and relevant stakeholders is needed, particularly in terms of capacity building, financial facilitation, and strengthening marketing strategies, so that MSMEs based on local wisdom can develop sustainably and remain competitive.